Analysis of Financial Performance of Village Fund Allocation Managers Based on Effectiveness Ratio and Growth Ratio at the Sipahutar III Village Office, Sipahutar District, North Tapanuli District - Dhiva Ayu Sharanie; Dito Aditia Darma Nasution (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to determine the effectiveness of financial performance growth in managing Village Fund Allocations (ADD) at the Sipahutar III Village Office, Sipahutar District, North Tapanuli Regency. The data used comes from the Village Fund Allocation Financial Report from 2020 to 2022. Data collection methods used include documentation, literature study and observation. The data analysis technique applied is descriptive statistics using effectiveness ratios and growth ratios. The research results show that the financial performance of Village Fund Allocation (ADD) at the Sipahutar III Village Office is categorized as effective or good in terms of effectiveness ratio, with an average effectiveness of 100% during the 2020-2022 period. However, in terms of income and expenditure growth, there was a decline with an average negative growth of -3%. This research provides an illustration that although the effectiveness of ADD management in Sipahutar III Village is good, the challenge lies in the growth of income and expenditure which shows a decline. The implications of this research can be used as a basis for improving financial management strategies in order to support better growth in the future